مسببات ظاهرة الفساد المالي والإداري وإستراتيجيات مكافحتها - بوفلفل, سهام (جامعة الوادي University of Eloued, 2021)
تهدف هذه الدراسة إلى تسليط الضوء على مشكلة الفساد المالي والإداري التي لا زالت تشغل بال الباحثين، باعتبارها من أهم القضايا البارزة في الوقت الحالي، لما لها من آثار سلبية على جميع مناحي الحياة من صحة وتعليم ومشاكل أخرى تضرب البنية الاقتصادية والاجتماعية، لهذا أصبح لزاما البحث عن سبل كفيلة بمعالجة هذه الظاهرة، لهذا عملت دول العالم على تكثيف الجهود الدولية لمحاربتها، عن طريق إصدار العديد من القوانين والإمضاء على العديد من الاتفاقيات الدولية الهادفة إلى الحد من انتشار هذه الظاهرة، ولتحقيق أهداف الدراسة تم تقسيم البحث إلى ثلاث محاور رئيسية حاولنا من خلالها التطرق إلى مختلف الجوانب النظرية للفساد والمالي والإداري من خلال المحور الأول، والتطرق إلى استراتيجيات مكافحة الفساد من خلال المحور الثاني، وجاء المحور الثالث بعنوان التجربة الجزائرية في مجال مكافحة الفساد، وخلصت هذه الدراسة إلى أن آثار الفساد المالي والإداري آثار جد سلبية تعمل على هدم البنية الاقتصادية والاجتماعية لذا وجب السعي الحثيث لمكافحتها. This study aims to shed light on the problem of financial and administrative corruption that still concerns researchers, as it is one of the most prominent issues at the present time, because of its negative effects on all aspects of life from health, education and other problems that affect the economic and social structure. about ways to address this phenomenon, which is why the countries of the world have worked to intensify international efforts to combat it,Through the issuance of many laws and the signing of many international agreements aimed at limiting the spread of this phenomenon, and to achieve the objectives of the study, the research was divided into three main axes through which we tried to address the various theoretical aspects of corruption, financial and administrative through the first axis, and to address strategies to combat corruption. Corruption through the second axis, and the third axis entitled the Algerian experience in the fight against corruption,This study concluded that the effects of financial and administrative corruption are very negative effects that destroy the economic and social structure, so it is necessary to strive to combat it.
The causes of the phenomenon of financial and administrative corruption and strategies to combat it (Algeria as a model)
مقال
Keywords: الفساد المالي والإداري، إستراتيجيات المكافحة، التجربة الجزائرية.; Keywords: financial and administrative corruption, combating strategies, the Algerian experience